A multi-center effectiveness comparison study of fruquintinib with constructed external control cohort of other targeted kinase inhibitors using real-world data in third-line treatment of metastatic colorectal cancer - Jin, Ying; Li, Jin; Shen, Lin; Xu, Jianming; Zhang, Yanqiao; Zhang, Jingdong; Pan, Hongming; Qu, Xiujuan; Chen, Yamin; Zhang, Qiang; Li, Jinnan; Sun, Miaomiao; et al. (Frontiers in Oncology, 2022)
Objective: The objective of this study was to assess the comparative efficacy in third-line setting for metastatic CRC (mCRC) patients using matched population of FRESCO trial with fruquintinib and real-world data with other TKIs. Materials and methods: The arm of fruquintinib from the FRESCO phase III trial (NCT02314819) included the data of patients with metastatic CRC that progressed after at least 2 lines of chemotherapy and received fruquintinib treatment. An external control arm was constructed using real-world data (RWD) of patients who received other TKIs based on key eligibility criteria of FRESCO. The baseline characteristics of two arms was balanced by propensity score matching (PSM). The Kaplan–Meier method and Cox proportional hazard model was used to evaluate progression free survival (PFS) and to estimate hazard ratios (HRs) and 95% confidence intervals (CIs), respectively. Results: Overall, 128 patients were successfully matched by PSM in each, fruquintinib and other TKIs group. The patients in fruquintinib group showed significant increase in median PFS than other TKIs (3.71 vs 2.49 months, HR = 0.67, 95%CI, 0.48-0.94, p = 0.019). In the subgroup analysis, fruquintinib showed a significant benefit in PFS compared with other TKIs among patients undergoing 2 or 3 previous chemotherapy regimens (HR 0.58, 95%CI 0.40-0.84; p=0.004), with rectum as primary disease site (HR 0.52, 95%CI 0.31-0.87; p=0.013), with left sided primary tumor location (HR 0.62, 95%CI 0.42-0.90; p=0.011), with multiple metastasis sites (HR 0.68, 95%CI 0.48-0.97; p=0.034) and with lung metastasis (HR 0.65, 95%CI 0.43-0.98; p=0.042). Conclusion: With the approach of establishing the external control arm from RWD, this study has demonstrated that treatment with fruquintinib significantly prolonged PFS as compared to other TKIs in patients as third-line mCRC treatment.